Capital Structure and Board Characteristics in Firm Performances of Indonesian LQ45 Companies - Saarce Elsye Hatane; Felicia Wiyono; Josua Tarigan (The Indonesian Journal of Accounting Research, 2020)
This study aims to examine the effects of capital structure, and board diversities toward the performance of the company measured through ROCE and EVA spread. The study is conducted on companies from various industries that are listed on the Indonesia Stock Exchange (in the LQ45 index) and published an annual report for 7 years from 2010 to 2016. Capital structure management and board diversities must be well managed so that the company can sustain and secure its position in the market in order to maximize shareholders’ wealth, which becomes a new corporate paradigm for the company. This study observes a total of 588 annual reports comprising of 84 companies from various industry over a period of 7 years. Total debt to total asset ratio is used for capital structure measure as an independent variable. Gender diversity and education levels diversity are be used to measure board diversities as the moderating variables and firm performances are assessed through ROCE as accounting profit measure and EVA spread as the market-based. There are three control variables, namely, sales growth, firm size and firm age. There are eight hypotheses to be tested in this study. The results of this study are quite diverse. Debt to total assets has significant negative impacts on ROCE and EVA. Gender diversity has no significant effect on ROCE but has a negative one on EVA. The diversity in education level also has no significant impact on ROCE but has a significant positive effect on EVA. Diversity in the educational background has a significant negative effect on ROCE but has no significant influence on EVA.